2013
DOI: 10.1111/jcpe.12102
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oral bacterial DNA in synovial fluid

Abstract: DNA of periodontopathogens can be found in synovial fluid and oral bacteria may play a role in the pathogenesis of arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 46 publications
2
84
0
7
Order By: Relevance
“…Moreover, P. gingivalis -derived LPS was also detected in the brains of AD patients (Poole, et al, 2013). It is accepted that periodontal bacteria can be found at distant sites (Cavrini, et al, 2005, Haraszthy, et al, 2000, Okuda, et al, 2001, Reichert, et al, 2013). These data indicate that peripheral inflammation/infections can lead to infection/inflammation in the brain and promote amyloid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, P. gingivalis -derived LPS was also detected in the brains of AD patients (Poole, et al, 2013). It is accepted that periodontal bacteria can be found at distant sites (Cavrini, et al, 2005, Haraszthy, et al, 2000, Okuda, et al, 2001, Reichert, et al, 2013). These data indicate that peripheral inflammation/infections can lead to infection/inflammation in the brain and promote amyloid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has implicated periodontal pathogens in the development and progression of RA (de Pablo, Chapple, Buckley, & Dietrich, ). Interestingly, increased antibody titers against P. gingivalis (Mikuls et al., ) and the DNA of oral bacterial, including P. gingivalis, have been detected in the serum and synovial fluid of RA patients (Martinez‐Martinez et al., ; Moen et al., ; Reichert et al., ). Case‐control studies found a more prevalent and severe periodontal disease (PD) status in RA patients (Al‐Shammari, Al‐Khabbaz, Al‐Ansari, Neiva, & Wang, ; Bozkurt, Yetkin Ay, Berker, Tepe, & Akkus, ), as well as a reduction in the clinical parameters of active RA following effective periodontal treatment and control of periodontal infection (Al‐Katma, Bissada, Bordeaux, Sue, & Askari, ; Bıyıkoğlu et al., ; Ortiz et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…P. gingivalis DNA was significantly more likely to be found in the synovial fluid of patients with RA than in controls (116), and interestingly the severity of periodontal disease (quantified by the number of missing teeth) in patients with RA was positively correlated with the number of affected joints. However, another study found only an association between P. gingivalis and the likelihood of developing and severity of periodontitis but no association with RA (117), and a third study found that P. gingivalis was more abundant in the oral cavity of controls compared to cases (113).…”
Section: Musculoskeletalmentioning
confidence: 99%